Akulturasi Budaya Islam dan India: Tinjauan Historis Terhadap Dialektika Kebudayaan Islam di India - Faidi, Ahmad (Warisan: Journal of History and Cultural Heritage, 2020)
This article discusses the acculturation of Islamic and Indian culture and syncretism of Islam and Hinduism in India. In particular, this article examines the transformation and acculturation of Islam, as the largest celestial religion in the world, with Indian values and culture so thick with Hindu values; the largest Ardli religion in the world. Through the Historical approach, this paper will present the process of historical dynamics between Islamic and Indian culture. The Divine Din, is one of the syncretic religious concepts - coined by Mahmud Ghazan Khan - which marks the collaboration of religion and culture in Indian society during the Mughal Dynasty.